Digital Green Waqf: A Systematic Literature Review on Sustainable Islamic Philanthropy in the Digital Era - Wali Saputra (Indo Publishing, 2025)
Eco-centric digital waqf, or digital green waqf, represents an innovative advancement in Islamic philanthropy that amalgamates the principles of sustainability with digital technologies to confront modern socio-ecological dilemmas. This investigation seeks to rigorously analyze the developments, trends, and research deficiencies in the extant literature pertaining to the digitization of waqf and its consequential application in furtherance of the sustainable development agenda. The methodology employed was a Systematic Literature Review (SLR) encompassing 80 scholarly articles sourced from accredited national journals and esteemed international journals (Scopus and WoS) during the period spanning 2010 to 2024. The findings of the study delineated four principal themes: (1) digitization of waqf management, (2) integration of green waqf within the sustainability agenda, (3) governance and innovation within the realm of Islamic philanthropic finance, and (4) constraints of regulation and implementation models concerning digital green waqf. The research revealed that while the potential of digital waqf to bolster a green economy is substantial, its practical execution remains largely confined to a conceptual framework. The deficiencies in regulatory measures, the digital literacy of wakif, and the requisite synergies among technology, nazhir institutions, and governmental bodies pose significant challenges. This study contributes by mapping the contemporary literature and proposing future research trajectories aimed at establishing a comprehensive and sustainable digital green waqf framework.